Options for agriculture at Marrakech climate talks: messages for SBSTA 45 agriculture negotiators - Dinesh, Dhanush; Vermeulen, Sonja J.; Bacudo I; Martínez Barón, Deissy; Castro Nuñez, Augusto; Hedger, Merylyn; Huyer, Sophia; Iversen, P.; Laure A; Loboguerrero Rodriguez, Ana María; Martius, Christopher; Neufeldt, Henry; et al. (2016)
SBSTA 45 in Marrakech represents a unique opportunity for Parties to decide on the future of agriculture within the UNFCCC. The process of discussions on issues related to agriculture initiated at COP17 in Durban 2011 culminates at COP22 in Marrakech 2016. The explicit reference to food security in the preamble of the Paris Agreement and the Intended Nationally Determined Contributions which prioritize agriculture as a sector for adaptation and mitigation actions, provide a foundation for Parties to develop appropriate frameworks to support actions within the agricultural sector. SBSTA workshops on agriculture in 2015 and 2016 allowed Parties to share experiences, identify priorities, and propose ways of taking action within the agricultural sector and so provide the core knowledge base to work from. As Parties reach a decision on issues related to agriculture at SBSTA 45, a number of options are available. This report presents ten such options that might contribute to a decision, taking into consideration political priorities, implementation arrangements, timelines and level of ambition. Options outlined in this report are not mutually exclusive and can be combined in many different ways.